Pengaruh Lama dan Waktu Peneduhan Terhadap Pertumbuhan dan Hasil Kacang Hijau Varietas Camar - Pamungkas, Djoko Heru (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
A study on the effect of length time shading (approx 70 % of sun rise intensity) to the growth and yield of Camar mung bean variety was conducted in Nogotirto, Gamping, Yogyakarta. The experiment was arranged in a Randomized Complete Block Design with 3 replications. The treatment were 6 levels of length and time of shading of Camar mung bean variety, i.e.: shading at the whole life cycles (A), the first half life cycles (B), the second half life cycles (C), the first quarter life cycles (D), the second quarter life cycles (E) and no shading at the whole life cycles or control (F).The result showed that the length and time of shading affected the growth and yield of Camar mung bean variety significantly except for the number of root - pimples, the number of effective root - pimples and weight of 100 grain per plant parameters. In accordance with the control, the shading at the first quarter and second quarter or at last life cycles gave no significant different in the growth and yield. The yield of that treatments ware 1.77, 1.72 and 1.82 tons seed per hectare. While in accordance with the control, the shading at the first half, the second half and at the whole life cycles gave the lower growth and yields. The decreasing at the yields were 28.95, 32.96 and 42.36 %.